A simple tool for the assessment of water quality in polluted lagoon systems: A case study for Kucukcekmece Lagoon, Turkey - Taner, Mehmet Umit; Ustun, Beyza; Erdincler, Aysen (ELSEVIER, 2011)
Lagoon systems have particular ecological, morphological and hydrodynamic characteristics and act like transitional zones between inland and open waters. The aim of this study is to develop a Lagoon Water Quality Index (L-WQI) for environmental control of polluted lagoon systems by focusing on primary problems such as increasing stress on aquatic biota, eutrophication and organic pollution. The indicators used in L-WQI are dissolved oxygen saturation, total nitrogen to total phosphorus ratio, nitrate, orthophosphate, chlorophyll-a, chemical oxygen demand, pH, turbidity and electrical conductivity. L-WQI establishes a new normalization function for each variable and uses a modified version of the weighted aggregation method. L-WQI has been adapted to Kucukcekmece Lagoon, a highly polluted watershed located in western Istanbul. The results correlated with the observed water quality trends in this lagoon and highlighted the impact of pollution in its tributaries. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Water Quality Index (WQI); Lagoon; Eutrophication; Water quality assessment; Kucukcekmece; INDEX; RIVER; Biodiversity & Conservation; Environmental Sciences & Ecology